Analisis Sistem Pengaturan Suhu Air Menggunakan Heater Berbasis Kontrol PID dan Kesalahan (Offset) pada Sistem Pemanas di Industri - Johan Prasetyo; Seflahir Dinata; Aripin Triyanto; Abdurahman Abdurahman (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Stable temperature regulation is essential in various industries to maintain product quality and energy efficiency. This study analyzed the water temperature regulation system using PID control through MATLAB simulation and the actual implementation using Thermocontrol and PT100 sensors. In the simulation, the PID control parameters used were Kp = 3.0, Ki = 240, and Kd = 60, while the tuning results in the actual implementation were Kp = 3.0, Ki = 0.5, and Kd = 1.2. The simulation results showed that the system could reach the setpoint faster (±330 seconds), but with a high overshoot (±20.8°C). In contrast, the actual implementation shows more stable performance, with a much lower overshoot (±0.8°C) and a time to the setpoint of about ±345 seconds. These differences in performance can be influenced by environmental factors and the physical characteristics of real systems that are not fully reflected in the simulation. Although the simulation provides faster results, the actual implementation is more adaptive to changing conditions and better able to maintain temperature stability. This research can provide important insights into the development of more effective and reliable temperature control systems for industrial applications, as well as demonstrate the importance of proper tuning in PID control systems to achieve optimal performance.